The Impact of Creative Digital Marketing on the Sustainability of MSME Businesses: A Mediating Role of Marketing Performance - Vania, Amelindha; Fikriah, Nur Laili (Universitas Pendidikan Nasional, 2023)
Creativity in digital marketing is essential in today's digital economy, where businesses need to adapt to the rapid changes brought by digital innovation. The declining trend in the contribution of MSMEs is worrying for the economy and the business world. MSMEs need to maximize digital marketing creativity for business continuity through the role of marketing performance. The aim of this research is to look at the role of creative digital marketing in improving the marketing performance and sustainability of MSMEs. This research uses explanatory quantitative methods with data analysis techniques, namely the SmartPLS 3.0 application. The object of this research is members of MSMEs assisted by Baznas Microfinance Malang with a sample of 170 MSMEs. The results of this research explain that creative digital marketing is able to improve marketing performance and business sustainability and the role of marketing performance is able to mediate between creative digital marketing and business sustainability. The contribution of this research to science is to determine the role of creativity in digital marketing management to improve marketing performance and business sustainability. It is very important to study each dimension of creative digital marketing so that it can be applied to all MSMEs, especially Baznaz-assisted MSMEs in Malang City.